The Connective Patterns of Experience Quality and Environmental Perception to Revisit Intentions in Creative Cultural Tourism - Gunawan, Arie Indra; Mustikasari, Ati; Agustina, Regina; Christianingrum; Februadi, Agustinus (Journal of Marketing Innovation (JMI), 2024)
Creative cultural tourism faces significant challenges due to its relatively standard offerings and the repetitive nature of its attractions. To remain competitive, the development of creative cultural tourism must adapt dynamically to evolving visitor demands. While several studies have explored aspects of creative tourism, they often fall short in assessing visitor needs. This study aims to fill that gap by investigating the specific needs of visitors in the context of creative cultural tourism. A cross-sectional method was employed, followed by a quantitative approach using data collected through questionnaires. The study gathered a total of 306 responses from visitors to Taichung's creative tourism sites in Taiwan, which were then analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research findings indicate that the quality of the experience has a direct influence on visitors' intention to revisit, while perceptions of the tourist environment significantly affect visitor satisfaction. These results suggest that the development of creative tourism should focus on enhancing value in ways that align with visitor desires, ensuring the experience remains authentic and engaging. By integrating high-quality experiences with positive environmental perceptions, destinations can attract and retain visitors more effectively.